2019
DOI: 10.1111/njb.02308
|View full text |Cite
|
Sign up to set email alerts
|

Do local conspecific density and floral display size influence fruit set via pollinator visitation in Orchis militaris?

Abstract: Plant density varies naturally, from isolated plants to clumped individuals, and this can influence pollinator foraging behaviour and plant reproductive success. In addition, the effect of conspecific density on reproduction may depend on the pollination system, and deceptive species differ from rewarding ones in this regard, a high density being often associated with low fruit set in deceptive plants. In our study, we aimed to determine how local conspecific density and floral display size (i.e. number of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Previous studies on orchid species showed that the inflorescence size (number of flowers per inflorescence) is one of the factors that affect the reproductive success, although fruit set does not always increase linearly with inflorescence size [ 2 ]. Numerous positive cases [ 5 , 12 , 30 , 31 ] and negative/uncorrelated cases [ 32 34 ] have been observed in orchid species. For the studied species, our results showed a positive correlation between the number of flowers developing into fruit and the number of flowers per inflorescence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on orchid species showed that the inflorescence size (number of flowers per inflorescence) is one of the factors that affect the reproductive success, although fruit set does not always increase linearly with inflorescence size [ 2 ]. Numerous positive cases [ 5 , 12 , 30 , 31 ] and negative/uncorrelated cases [ 32 34 ] have been observed in orchid species. For the studied species, our results showed a positive correlation between the number of flowers developing into fruit and the number of flowers per inflorescence (Fig.…”
Section: Discussionmentioning
confidence: 99%